The conservation history of the mausoleum of Shajarat al-Durr - Shoukry, Farah (AUC Knowledge Fountain, 2016)
This M.A. thesis aims to critically analyze the conservation history of the mausoleum of Shajarat al-Durr. Although Shajarat al-Durr’s biography is a well-published topic in the field of Islamic History, her only surviving architectural patronage lacks comprehensive documentation for its conservation schemes through history. The first chapter presents the biography of the sultāna in relation to the architectural analysis of the mausoleum. The second chapter investigates the theoretical concepts of conservation from an Islamic history point of view. Chapter three traces the conservation history of the mausoleum with a focus on the work of the Comité. The fourth chapter evaluates a more modern conservation practice with the theme of community participation that is currently taking place in al-Khalīfa under the name of Athar Lina project. The last chapter provides a summary of the research work identifying gaps in the study. It also discusses the accumulated challenges of conserving the mausoleum of Shajarat al-Durr as presented in history and identifies a number of related areas worthy of study. Documenting the conservation work in an accessible manner to the world of Islamic art and architecture is recommended to perceive monuments in a more authentic light. The Conservation History of the Mausoleum of Shajarat al-Durr serves as a research example highlighting the timeliness of monuments and how they evolve over time.